Long-term care administration and management : effective practices and quality programs in eldercare - Yee-Melichar, Darlene; Flores, Cristina M.; Cabigao, Edwin P. (Springer Publishing Company, LLC, 2014)
This is a comprehensive reference for long-term care administrators, practitioners and students who want to understand the options, issues, and trends related to the effective administration and management of long-term care communities. The book is unique in its in-depth focus on what needs to be accomplished and the evidence-based information about what actually works. Multifaceted insights address the ever-changing world of the long-term care industry and offer best practices and model programs in eldercare. . This multidisciplinary book covers the most crucial aspects of management includi.